TINGKAT PERKEMBANGAN DAN PRIORITAS PENGEMBANGAN KELOMPOK MASYARAKAT PENGAWAS DUURSTEDE KECAMATAN SAPARUA - Yoisye Lopulalan; Yofita Anaktototy (Universitas Pattimura, 2025)
Sustainable management of marine and fisheries resources requires active community participation, particularly through community supervisory groups. This study aims to analyze the development level and determine the development priorities of the community supervisory group Duurstede in Saparua District. The research was conducted from June to August 2024 using qualitative methods through interviews, questionnaires, and focus group discussions involving all the members (40 respondents). Institutional analysis employed the Institutional Development Framework to assess six resource characteristics: vision development, management, human resources, finance, external relations, marine–fisheries surveillance, and infrastructure. The results show that the development level of the community supervisory group Duurstede remains at the initial stage (40.35%), with smaller portions of components at the developing stage (19.30%), consolidation stage (22.81%), and sustainability stage (17.54%). This study concludes that the community supervisory group Duurstede requires comprehensive institutional strengthening, particularly in the provision of infrastructure, operational funding, and capacity-building for its members. The government and supporting institutions are recommended to enhance guidance, training, and facility support to improve the effectiveness of the community supervisory groups in marine and fisheries resource surveillance.